Peningkatan Motivasi Belajar Siswa melalui Model Pembelajaran Picture And Picture pada Materi Muatan IPS Di Sekolah Dasar - Heny Prihatiniwati; Sukadari Sukadari (Proceedings Series on Social Sciences & Humanities, 2022)
Low learning motivation of student at elementary schools becomes a problem for students as well as teacher. Low motivation will affect the students’ achievement. This also will make teachers difficult to meet the learning aims. This problem needs solution. Teachers need to use contain models of teaching and learning activities in order to improve the students’ motivation. One of model used by the writer is picture and picture model. Picture and picture model of teaching and learning is model in which teacher use pictures as the main component. Briefly, students should arrange the picture. Chronologically in order that they become a story. Students do this activity in groups. Using the picture and picture model of teaching and learning result in the higher motivation of students in learning. In addition, the teaching learning activity become more interesting to students.